Pengaruh Profitabilitas, Leverage dan Ukuran Perusahaan Terhadap Tax Avoidance pada Perusahaan Sub Sektor Industrial Goods yang Terdaftar di Bursa Efek Indonesia (BEI) - Deswita Maharani; Henny Triastuti Kurnia Ningsih; Lusi Elviani Rangkuti (Universitas Islam Islam Sumatera Utara, 2026)
This study aims to examine and analyze the effect of profitability, leverage, and firm size on tax avoidance in industrial goods sub-sector companies listed on the Indonesia Stock Exchange during the 2022–2025 period. The research employed a quantitative approach using secondary data obtained from the companies' financial statements. The population consisted of 42 companies, while 32 companies were selected as samples using purposive sampling, resulting in 128 observations. Data were analyzed using descriptive statistics, classical assumption tests, multiple linear regression, t-test, F-test, and coefficient of determination. The results indicate that profitability and leverage have a positive and significant effect on tax avoidance. Firm size has a positive but insignificant effect on tax avoidance. Simultaneously, profitability, leverage, and firm size significantly affect tax avoidance in industrial goods sub-sector companies listed on the Indonesia Stock Exchange.